EXPENDITURE MANAGEMENT AND CONTROL IN BULGARIAN MUNICIPALITIES IN THE CONTEXT OF THEIR FINANCIAL HEALTH - Ivanova, Diyana (E-Journal VFU, 2025)
The good financial state of budgetary organizations is a necessary prerequisite for the stable and sustainable development of the public sector and for the successful implementation of its socially significant function. This determines the relevance of the topic of financial management and control of budgetary organizations and the need for analyzing and assessing them. The study focuses specifically on municipal expenditure commitments, which bind municipalities to future expenditure payments and/or new expenditure obligations and have an impact on their financial health in the subsequent reporting periods.